Recent Advances on Design and Synthesis of Chiral Imidazolium Ionic Liquids and their Applications in Green Asymmetric Synthesis - Saha, Arijit; Payra, Soumen; Banerjee, Subhash (Journal of Applied Solution Chemistry and Modeling, 2016)
Over the past decade, catalysis by ionic liquids (ILs) has experienced a tremendous growth in the context of â€œGreen Chemistryâ€, and there are numerous examples of a variety of catalytic reactions that have been successfully carried out in such neoteric media.The great enthusiasm for catalysis in ILs is not only driven by the curiosity of chemists, but also due to the growing awareness of developing greener reactions or process media in catalytic science and greener catalytic technologies due their advantages of unique physical and chemical properties as compared to traditional volatile organic solvents.Recently, development of chiral ionic liquids and their applications in asymmetric synthesis have attracted much attention as these reactions have widespread applications in the synthesis of chiral drugs and pharmaceutical industries. Asymmetric induction is mainly achieved by the use of chiral substrates or reagents, chiral catalysts or enzymes. Owing to the vast number of structurally different room temperature ILS that have been synthesized, this review focuses on imidazolium ionic liquids that possess chirality either in the imidazolium moiety or in the anion moiety. The aim of this review is to highlight the recent breakthrough of Chiral ILs in chirality transfer or chiral recognition when used as solvent or co-solvent: the case of task specific ionic liquids is beyond the scope of this review. In the first part, the synthesis of of CILs has been presented and the second part of the review has been devoted on the applications of such CILs in green asymmetric synthesis as well as various pharmaceutical industries.